22q11.2q13 duplication including SOX10 causes sex-reversal and peripheral demyelinating neuropathy, central dysmyelinating leukodystrophy, Waardenburg syndrome, and Hirschsprung disease. - Falah, Nadia; Posey, Jennifer E; Thorson, Willa; Benke, Paul; Tekin, Mustafa; Tarshish, Brocha; Lupski, James R; Harel, Tamar (Am J Med Genet A, 2017)
Diagnosis of genetic syndromes may be difficult when specific components of a disorder manifest at a later age. We present a follow up of a previous report [Seeherunvong et al., (2004); AJMGA 127: 149-151], of an individual with 22q duplication and sex-reversal syndrome. The subject's phenotype evolved to include peripheral and central demyelination, Waardenburg syndrome type IV, and Hirschsprung disease (PCWH; MIM 609136). DNA microarray analysis defined the duplication at 22q11.2q13, including SOX10. Sequencing of the coding region of SOX10 did not reveal any mutations. Our data suggest that SOX10 duplication can cause disorders of sex development and PCWH, supporting the hypothesis that SOX10 toxic gain of function rather than dominant negative activity underlies PCWH.
Keywords: 46, XX Testicular Disorders of Sex Development; African Americans; Chromosome Duplication; Chromosomes, Human, Pair 22; Demyelinating Diseases; Hirschsprung Disease; Humans; Kidney Failure, Chronic; Male; Pelizaeus-Merzbacher Disease; SOXE Transcription Factors; Waardenburg Syndrome

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Yuan, Bo; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Mechanisms for the Generation of Two Quadruplications Associated with Split-Hand Malformation. - Gu, Shen; Posey, Jennifer E; Yuan, Bo; Carvalho, Claudia M B; Luk, H M; Erikson, Kelly; Lo, Ivan F M; Leung, Gordon K C; Pickering, Curtis R; Chung, Brian H Y; Lupski, James R (Hum Mutat, 2016)
Germline copy-number variants (CNVs) involving quadruplications are rare and the mechanisms generating them are largely unknown. Previously, we reported a 20-week gestation fetus with split-hand malformation; clinical microarray detected two maternally inherited triplications separated by a copy-number neutral region at 17p13.3, involving BHLHA9 and part of YWHAE. Here, we describe an 18-month-old male sibling of the previously described fetus with split-hand malformation. Custom high-density microarray and digital droplet PCR revealed the copy-number gains were actually quadruplications in the mother, the fetus, and her later born son. This quadruplication-normal-quadruplication pattern was shown to be expanded from the triplication-normal-triplication CNV at the same loci in the maternal grandmother. We mapped two breakpoint junctions and demonstrated that both are mediated by Alu repetitive elements and identical in these four individuals. We propose a three-step process combining Alu-mediated replicative-repair-based mechanism(s) and intergenerational, intrachromosomal nonallelic homologous recombination to generate the quadruplications in this family.
Keywords: 14-3-3 Proteins; Adult; Aged; Alu Elements; Base Sequence; Basic Helix-Loop-Helix Transcription Factors; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; Female; Genetic Loci; Genome, Human; Hand Deformities, Congenital; Humans; Infant; Male; Molecular Sequence Data; Pedigree; Sequence Alignment; Sequence Analysis, DNA

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Yuan, Bo; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Transcription Factors

Gigantism and acromegaly due to Xq26 microduplications and GPR101 mutation. - Trivellin, Giampaolo; Daly, Adrian F; Faucz, Fabio R; Yuan, Bo; Rostomyan, Liliya; Larco, Darwin O; Schernthaner-Reiter, Marie Helene; Szarek, Eva; Leal, Letícia F; Caberg, Jean-Hubert; Castermans, Emilie; Villa, Chiara; et al. (N Engl J Med, 2014)
BACKGROUND: Increased secretion of growth hormone leads to gigantism in children and acromegaly in adults; the genetic causes of gigantism and acromegaly are poorly understood. METHODS: We performed clinical and genetic studies of samples obtained from 43 patients with gigantism and then sequenced an implicated gene in samples from 248 patients with acromegaly. RESULTS: We observed microduplication on chromosome Xq26.3 in samples from 13 patients with gigantism; of these samples, 4 were obtained from members of two unrelated kindreds, and 9 were from patients with sporadic cases. All the patients had disease onset during early childhood. Of the patients with gigantism who did not carry an Xq26.3 microduplication, none presented before the age of 5 years. Genomic characterization of the Xq26.3 region suggests that the microduplications are generated during chromosome replication and that they contain four protein-coding genes. Only one of these genes, GPR101, which encodes a G-protein-coupled receptor, was overexpressed in patients' pituitary lesions. We identified a recurrent GPR101 mutation (p.E308D) in 11 of 248 patients with acromegaly, with the mutation found mostly in tumors. When the mutation was transfected into rat GH3 cells, it led to increased release of growth hormone and proliferation of growth hormone-producing cells. CONCLUSIONS: We describe a pediatric disorder (which we have termed X-linked acrogigantism [X-LAG]) that is caused by an Xq26.3 genomic duplication and is characterized by early-onset gigantism resulting from an excess of growth hormone. Duplication of GPR101 probably causes X-LAG. We also found a recurrent mutation in GPR101 in some adults with acromegaly. (Funded by the Eunice Kennedy Shriver National Institute of Child Health and Human Development and others.).
Keywords: Acromegaly; Adolescent; Adult; Age of Onset; Child; Child, Preschool; Chromosome Duplication; Chromosomes, Human, X; Female; Gigantism; Human Growth Hormone; Humans; Infant; Male; Mutation; Phenotype; Protein Conformation; Receptors, G-Protein-Coupled